A mediação pedagógica na educação teológica a distância: um estudo de caso - Santo, Eliseu Roque do Espirito (2010)
This work analyzes the pedagogical mediation of theological education using distance education. The method is qualitative research with a specialization in pedagogical research using a case study strategy. The work seeks to analyze the pedagogical mediation using three basic virtual environment tools which are web-class texts in PDF, video-classes and learning activities. Seven disciplines from the curriculum of a theological program were selected for analysis: Christian Counseling, Communication and Homiletics, Religious Teaching and Basic Education, Basics in Practical Theology, Practical Ministries, Theology and Leadership, Spiritual Formation (Spirituality). To begin with, a definition of the categories to be analyzed was sought, along with the construction of observation protocols. As a parameter for analysis, the researcher sought to follow three phases of mediation presented by Gutierrez and Prieto: a treatment of the subject matter, a treatment of the form (visual communication) and a treatment of the learning. To analyze the video-classes, it was necessary to define a new category, a treatment of the function. In the case of the web-class tool the content of fifty eight texts was analyzed using the categories of a treatment of the subject matter and a treatment of the form (visual communication). In the case of the video-classes, ten videos were watched and transcribed so they could be analyzed using the categories of a treatment of the subject area, a treatment of the form (visual communication) and a treatment of the function. Learning activities, including written tests, were analyzed under the category a treatment of learning. As a result of the research, it can be noted: (1) the tendency towards a movement from the format of classroom learning to distance education already registered in literature; (2) the tendency for the video-class to replace the classroom experience and, therefore, the necessity for a pedagogical architecture to elaborate the video-classes so that a treatment of the subject matter and the form (visual communication) as well as the content transmitted facilitate auto-learning and explore the real potential of this tool; (3) the tendency of the web-class texts to use the format of an academic text which points to the necessity of a pedagogical framework that favors auto-learning and that carefully elaborates the treatment of the form and subject matter; (4) learning activities predominate the type of appropriation of the content with rare occurrences of activities that promote inter-learning, textual-contextual relationships and applicability. Finally, based on the research, the researcher concluded that for authentic distance education to exist, it is not enough to just have technological mediation for the teaching-learning process. What is needed is a solid and well-planned pedagogical mediation.